2019
DOI: 10.1039/c8nj05905e
|View full text |Cite
|
Sign up to set email alerts
|

Random D1–A1–D1–A2 terpolymers based on diketopyrrolopyrrole and benzothiadiazolequinoxaline (BTQx) derivatives for high-performance polymer solar cells

Abstract: The overall power conversion efficiency of the polymer solar cell based on P13 (DPP/BTQx ratio is 1/1) showed the highest value of 9.20% with a Voc of 0.86 V, Jsc of 15.74 mA cm−2, and FF of 0.68.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…To address this problem, new D-A1-D-A2-type polymer donors using two kinds of accepting building blocks, DPP and BTQx, were developed to modulate the optical bandgap and its photovoltaic properties. 72 for CDT-FBSE and 0.24% for CDT-PSE, the broad photoresponse wavelength over 1,000 nm has great potential for NIR applications.…”
Section: Bt-based Narrow-bandgap Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…To address this problem, new D-A1-D-A2-type polymer donors using two kinds of accepting building blocks, DPP and BTQx, were developed to modulate the optical bandgap and its photovoltaic properties. 72 for CDT-FBSE and 0.24% for CDT-PSE, the broad photoresponse wavelength over 1,000 nm has great potential for NIR applications.…”
Section: Bt-based Narrow-bandgap Polymersmentioning
confidence: 99%
“…Sharma et al reported benzothiadiazole quinoxaline (BTQx) derivatives. 72,73 The strong electron-accepting building block BTQx, in which the Qx derivative is fused onto the BT, is a suitable candidate to narrow the band gap because it can easily induce a stabilized quinoidal resonance form. Among the BTQx derivatives, fluorene-substituted BTQx and the corresponding polymers (BT-P3 and BT-P4) were designed and developed.…”
Section: Narrow-band Gap Polymer Donor Materials For Nir Organic Sola...mentioning
confidence: 99%
See 2 more Smart Citations
“…A series of terpolymers (P51-P55) ( Figure 6) were synthesized by mixing different feed amounts of monomers based on benzothiadiazolequinoxaline (BTQx), DPP and BDT based molecular units (Keshtov et al, 2019). P51 and P55 are reference polymers with no BTQx and DPP, respectively.…”
Section: Quinoxaline Ring Based Polymersmentioning
confidence: 99%